2008
DOI: 10.1097/shk.0b013e31815072c1
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Observational Study of Soluble FLT-1 and Vascular Endothelial Growth Factor in Sepsis

Abstract: Prior murine and human studies suggest that vascular endothelial growth factor (VEGF) contributes to endothelial cell activation and severity of illness in sepsis. Furthermore, circulating levels of soluble VEGF receptor 1 (sFLT) levels were found to increase as part of the early response to sepsis in mice. The objective of the study was to evaluate the blood levels of free VEGF-A and sFLT in patients presenting to the emergency department (ED) with suspected infection and to assess the relationship of these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 20 publications
11
104
1
3
Order By: Relevance
“…The weaknesses of this study include the limited number of late blood specimens and the bundling of samples. Of note, human and animal studies have shown that proinflammatory conditions such as pneumonia, adult respiratory distress syndrome (ARDS), and sepsis increase plasma levels of VEGF and sVEGFR1 [28][29][30][31][32]. MICR-related complications might also influence postoperative levels of sVEGFR1 and sVEGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…The weaknesses of this study include the limited number of late blood specimens and the bundling of samples. Of note, human and animal studies have shown that proinflammatory conditions such as pneumonia, adult respiratory distress syndrome (ARDS), and sepsis increase plasma levels of VEGF and sVEGFR1 [28][29][30][31][32]. MICR-related complications might also influence postoperative levels of sVEGFR1 and sVEGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF causes endothelial permeability and proliferation, and may have pro-inflammatory effects by promoting adhesion of leukocytes to the endothelium. VEGF has recently been demonstrated to have an important role in the pathogenesis of sepsis, and increased levels of VEGF are related to a worsening organ dysfunction in septic patients [44]. Therefore, VEGF inhibition strategies may represent novel therapeutic targets in sepsis, whose downstream consequences may be achieved by improved microcirculatory flow.…”
Section: Future Therapeutic Directionsmentioning
confidence: 99%
“…A soluble form of Flt-1 (sFlt-1) is shed from the endothelial membrane and acts as a decoy receptor that inhibits VEGF signaling. Both Ang/Tie2 system (14,19,20) and the VEGF/ VEGFR system (18,21,22) are involved in endothelial activation in organ failure (23). Several reports have been published about angiogenic and vascular leakageY related factors and their soluble receptors in patients with chronic heart failure (22), yet comprehensive data in patients undergoing on-pump versus off-pump CABG surgery are scarce.…”
Section: Introductionmentioning
confidence: 97%